Preliminary Investigation of the Neurobehavioral Effects of Cinnamomum tamala Leaf Extract Through Behavioral Models and Molecular Docking - Bilkis, -; Hussain, Mohammad Musarraf (Bangladesh Pharmaceutical Journal, 2026)
Cinnamomum tamala is a traditionally used medicinal plant for many medical purposes; however, its neuropharmacological potential has not been properly studied. Using in vivo behavioral models and in silico molecular docking this study investigated the potential antidepressant and anxiolytic effects of the ethanolic leaf extract of C. tamala. Preliminery phytochemical screening identified the presence of alkaloids, flavonoids, phenols, tannins, saponins and glycosides. Behavioral evaluations were conducted using the tail suspension test (TST), forced swim test (FST) and open field test (OFT). While extract-treated groups showed trends toward decreased immobility in the TST and FST and no statistically significant differences were found when compared to the control group (p > 0.05). The extract also did not produce significant anxiolytic-like effects in the OFT. In contrast, favorable binding affinities and stable interactions of specific phytoconstituents (e. g. β-Caryophyllene, coumarin and α-humelene) with key amino acid residues were shown by molecular docking analysis against the human serotonin transporter (PDB ID: 5I6X) which is comparable to the reference drug, fluoxetine. Overall, even though C. tamala extract did not exhibit any notable behavioral effects in the current experimental setup but the in-silico findings suggest potential serotonergic involvement warranting further investigation with optimized experimental designs. Bangladesh Pharmaceutical Journal 29(1): 68-80, 2026 (January)